Facile Synthesis of Pt-Functionalized SnO2 Hollow Hemispheres and Their Gas Sensing Properties - Cho, Nam Gyu; Whitfield, George C.; Yang, Dae Jin; Kim, Ho-Gi; Tuller, Harry L.; Kim, Il-Doo (ELECTROCHEMICAL SOC INC, 2010)
This work presents a new route for enhancing the sensor response kinetics of macroporous SnO2 films. Well-ordered arrays of SnO2 hollow hemispheres, functionalized with catalytic Pt, were synthesized using colloidal templating and cosputtering, followed by subsequent heat-treatment. The diameter and shell thickness of the Pt-functionalized SnO2 hollow hemispheres were 800 and 25 nm, respectively. High resolution transmission electron microscopy analysis indicates that catalytic Pt nanoparticles, with size of a few nanometers, coat the top surface of SnO2 hemispheres, enabling chemical reactions to proceed at lower temperatures. Sensors composed of Pt-functionalized SnO2 hollow hemispheres show attractive gas sensing characteristics, such as reduced operation temperature (<= 250 degrees C) combined with improved sensitivity (R/R-o = 4.08 to 250 ppm H-2), reduced baseline resistance, and enhanced response/recovery properties compared to sensors using pristine SnO2 hollow hemispheres at an operating temperature of 250 degrees C. (C) 2010 The Electrochemical Society. [DOI: 10.1149/1.3489949] All rights reserved.
Keywords: CHEMICAL-MODIFICATION; OXIDE FILMS; THIN-FILMS; SENSORS; SURFACE; NANOSTRUCTURES; SENSITIVITY; XPS